Medium access control of multimedia CDMA systems with effective spectral bandwidth distribution - PAN Su1; FENG Guang-zeng1 (Tongxin xuebao)
A medium access control（MAC） protocol with effective spectral bandwidth distribution was proposed for the CDMA network carrying multi-service traffics.Based on the “BER limited” characteristics of the CDMA system,the protocol maps the diverse BER requirements of multimedia services into the effective spectral bandwidth.The ef-fective bandwidth was dynamically distributed to different services according to the traffic of the system.The simu-lation results show that the performance of the proposed system in terms of throughput is better than that of the exist-ing systems.